Realistic Mathematics Education (RME) Sebagai Sebuah Pendekatan pada Pengembangan Modul Matematika Berbasis Teori Multiple Intelligences Howard Gardner - Faidah, Nuzulul; Masykur, Ruhban; Andriani, Siska; Haerlina, Lina (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to develop modules based on the Multiple Intelligences Theory of Howard Gardner using the Realistic Mathematics Education (RME) approach in class VIII Middle School. This research is an R and D research which stages using the development of Borg and Gall. The instrument used in this study uses a questionnaire given to material experts and media experts to test the feasibility of this module. The research results that have been developed are feasible to be used in proper learning are used seen from the results of the validation of material experts and media experts. On the results of the media expert test obtained an average of 80% with the Criteria "Good" while the results of the material expert test obtained an average value of 84% with the criteria "Very Good". Student responses to the small group test obtained an average value of 79% with the criteria "Good", while the response of students in the field test obtained an average value of 88% with the criteria "Very Good".  Abstrak: Penelitian ini bertujuan untuk mengembangkan modul berbasis Teori Multiple Intelligences Howard Gardner menggunakan pendekatan Realistic Mathematics Education (RME) di kelas VIII SMP. Penelitian ini merupakan penelitian R and D yang tahapannya menggunakan pengembangan Borg and Gall. Instrumen yang digunakan dalam penelitian ini menggunakan angket yang diberikan kepada ahli materi dan ahli media untuk menguji kelayakan modul ini.Hasil penelitian yang telah dikembangkan layak digunakan dalam pembelajaran layakdigunakandilihat dari hasil validasi ahli materi dan ahli media. Pada hasil uji ahli media diperoleh rata-rata sebesar 80% denganKriteria “Baik” sedangkan pada hasil uji ahli materi diperoleh nilai rata-rata sebesar 84% dengankriteria “BaikSekali”. Adapun respon siswa pada  uji kelompok kecil diperoleh nilai rata-rata sebesar 79% dengan kriteria “Baik”, sedangkan respon siswa pada uji lapangan diperoleh nilai rata-rata sebesar 88% dengan kriteria “Baik Sekali”.